Mister Exam
Lang:
EN
EN
ES
RU
Other calculators:
Integral Step by Step
Derivative Step by Step
Differential equations Step by Step
How to use it?
Limit of the function
:
Limit of -35-14*x-6*x^2
Limit of (-exp(-x)-2*x+exp(x))/(x-sin(x))
Limit of (e^(5*x)-e^x)/(x^3+asin(x))
Limit of (3-4*x^2+8*x^4)/(1+2*x^4)
Integral of d{x}
:
1/(2-x)
Graphing y =
:
1/(2-x)
Identical expressions
one /(two -x)
1 divide by (2 minus x)
one divide by (two minus x)
1/2-x
1 divide by (2-x)
Similar expressions
-1/2-x-3*x/(-8+2*x^2)
1/(2+x)
Limit of the function
/
1/(2-x)
Limit of the function 1/(2-x)
at
→
Calculate the limit!
v
For end points:
---------
From the left (x0-)
From the right (x0+)
The graph:
from
to
Piecewise:
{
enter the piecewise function here
The solution
You have entered
[src]
1 lim ----- x->2+2 - x
lim
x
→
2
+
1
2
−
x
\lim_{x \to 2^+} \frac{1}{2 - x}
x
→
2
+
lim
2
−
x
1
Limit(1/(2 - x), x, 2)
Lopital's rule
There is no sense to apply Lopital's rule to this function since there is no indeterminateness of 0/0 or oo/oo type
The graph
-4.0
-3.0
-2.0
-1.0
4.0
0.0
1.0
2.0
3.0
-200
200
Plot the graph
Other limits x→0, -oo, +oo, 1
lim
x
→
2
−
1
2
−
x
=
−
∞
\lim_{x \to 2^-} \frac{1}{2 - x} = -\infty
x
→
2
−
lim
2
−
x
1
=
−
∞
More at x→2 from the left
lim
x
→
2
+
1
2
−
x
=
−
∞
\lim_{x \to 2^+} \frac{1}{2 - x} = -\infty
x
→
2
+
lim
2
−
x
1
=
−
∞
lim
x
→
∞
1
2
−
x
=
0
\lim_{x \to \infty} \frac{1}{2 - x} = 0
x
→
∞
lim
2
−
x
1
=
0
More at x→oo
lim
x
→
0
−
1
2
−
x
=
1
2
\lim_{x \to 0^-} \frac{1}{2 - x} = \frac{1}{2}
x
→
0
−
lim
2
−
x
1
=
2
1
More at x→0 from the left
lim
x
→
0
+
1
2
−
x
=
1
2
\lim_{x \to 0^+} \frac{1}{2 - x} = \frac{1}{2}
x
→
0
+
lim
2
−
x
1
=
2
1
More at x→0 from the right
lim
x
→
1
−
1
2
−
x
=
1
\lim_{x \to 1^-} \frac{1}{2 - x} = 1
x
→
1
−
lim
2
−
x
1
=
1
More at x→1 from the left
lim
x
→
1
+
1
2
−
x
=
1
\lim_{x \to 1^+} \frac{1}{2 - x} = 1
x
→
1
+
lim
2
−
x
1
=
1
More at x→1 from the right
lim
x
→
−
∞
1
2
−
x
=
0
\lim_{x \to -\infty} \frac{1}{2 - x} = 0
x
→
−
∞
lim
2
−
x
1
=
0
More at x→-oo
One‐sided limits
[src]
1 lim ----- x->2+2 - x
lim
x
→
2
+
1
2
−
x
\lim_{x \to 2^+} \frac{1}{2 - x}
x
→
2
+
lim
2
−
x
1
-oo
−
∞
-\infty
−
∞
= -151.0
1 lim ----- x->2-2 - x
lim
x
→
2
−
1
2
−
x
\lim_{x \to 2^-} \frac{1}{2 - x}
x
→
2
−
lim
2
−
x
1
oo
∞
\infty
∞
= 151.0
= 151.0
Rapid solution
[src]
-oo
−
∞
-\infty
−
∞
Expand and simplify
Numerical answer
[src]
-151.0
-151.0
The graph